ESTUDO DE ÍNDICES DE DIVERSIDADE COMO DESCRITORES DE TEXTURA PARA CLASSIFICAÇÃO DE IMAGENS DE FACES - Reis, Artur Bernardo Silva (2012)
This work purposes an investigation into the potential of characterization of textures of human faces in digital images using the diversity index. To this we developed a methodology that uses the retinex to normalization of lighting conditions, diversity indexes for feature extraction and Support Vector Machine as classifier. Several tests are performed using four bases of face images, each base with uniques characteristics that can be verified the usability of the indexes used. The results are very promising since in eighteen tests were reached accuracies over 95%. In addition, a sensitivity of 100% in a test case and false positive rate of 0.2%, indicating that the diversity index can be a good tool for describing textures of human faces.